PIXSIC, a pixelated β⁺-sensitive probe for radiopharmacological investigations in rat brain: binding studies with [¹⁸F]MPPF. - Balasse, L; Maerk, J; Pain, F; Genoux, A; Fieux, S; Morel, C; Gisquet-Verrier, P; Zimmer, L; Lanièce, P (Molecular Imaging & Biology, 2015)
Purpose: The aim of this work was to demonstrate the pharmacokinetic potential of a wireless pixelated β(+)-sensitive probe (PIXSIC).Procedures: The binding of 2'-methoxyphenyl-(N-2'-pyridinyl)-p-[(18)F]fluoro-benzamidoethylpiperazine ([(18)F]MPPF), a 5-HT1A serotonin receptor radiopharmaceutical, was measured in anesthetized rats and compared to microPET data. The effects of a 5-HT1A antagonist injection on in vivo [(18)F]MPPF binding were monitored by PIXSIC.Results: PIXSIC allowed differentiating the radioactive kinetics according to the location of its pixels in the hippocampus, cortex, corpus callosum, and cerebellum. The device accurately detected the changes in [(18)F]MPPF binding, after 5-HT1A antagonist blockade. The time-activity curves were reproducible and consistent with kinetics obtained simultaneously with a microPET camera.Conclusions: These results demonstrate the ability of the PIXSIC device to record reliably the binding of PET ligands, with a high spatiotemporal resolution in anesthetized rodents. These first in vivo results are a key stage on the path to its implementation in awake freely moving animals.